HOUSEHOLD ATTRIBUTES IN THE PREVENTION AND MANAGEMENT OFASTHMA IN CHILDREN ATTENDING SELECTED HOSPITALS IN IBADAN, NIGERIA (2023)
Asthma is one of the most prevalent non-communicable respiratory diseases in less developed countries. Nigeria ranks 49th in asthma prevalence among children worldwide. Previous studies have focused on asthma triggers and the seasonal pattern of asthma in children, yet they have not examined the influence of household attributes and activities on asthma prevention and management among children. This study was, therefore, designed to examine the perceived factors responsible for asthma in children, perceived household attributes and activities influencing its prevention and management, the influence of intergenerational factors and the pathways for seeking care for children living with asthma in Ibadan.The Health Belief Model served as the framework, while cross-sectional survey design was employed. The University College Hospital (Tertiary Hospital), Adeoyo Maternity Hospital (State Hospital), while Our Lady of Apostles Catholic Hospital (Private Hospital) were purposively selected. A sample of 273 respondents was drawn using Cochran (1977) formula. Purposive sampling was used to administer a structured questionnaire to parents of children aged 6 to 14 years, and physician-diagnosed asthma patients attending asthma clinics comprising UCH (124), Adeoyo Maternity Hospital (84) and Our Lady of Apostles Catholic Hospital (65). In-depth interviews were conducted with 10 children living with asthma in each of the hospitals, while Key Informant Interviews were also conducted with health practitioners in each of the hospitals. Six case studies were conducted with grandparents of children living with asthma to probe the influence of intergenerational factors. The Quantitative data were analysed using descriptive and inferential (chi-square and logistic regression) statistics at p≤0.05, while the qualitative data were content analysed.The Respondents’ age was 37±5.7years, 87.2% were female, while 63.8% had tertiary education. A majority (67.0%) lived in rented houses, while 69.6% used upholstered furniture and 73.6% used asbestos as roofing material. Nearly half (45.9%) perceived asthma to be caused by environmental factors (dust, smoke and weather conditions), inherited factors (37.5%), spiritual attack (13.0%), and punishment for sin (3.5%). Cooking methods (90.1%), cooking fuel (79.1%) and poor ventilation (72.9%) were reported as household attributes triggering asthma in children. Activities such as frying (χ2=6.00), baking (χ2=6.30) and laundry (χ2=7.14) were significantly associated with regularity of asthma attacks. The respondents’ religion (χ2=10.26), income (χ2=29.58), family type (χ2=15.18), ownership of house (χ2=8.77), type of house (χ2=23.88), education (χ2=52.07), household size (χ2=18.14), age of children living with asthma (χ2=6.14), occupation (χ2=18.60) and household decision making (χ2=4.20) were significantly related to treatment pathways. Family history of asthma was vital in its management in children. Grandparents’ experiences of use of natural home remedies such as honey, pawpaw leaves, camphor, mango seeds and turmeric were reported in the management of children with asthma. Household attributes and activities of children living with asthma in Ibadan influenced the prevention of asthma and was moderated by socio economic status, while natural home remedies were used in the management of asthma. Households with children living with asthma should improve housing conditions and cooking technologies.